El simulador de crecimiento y producción forestal PLAFORNEA - Keller, Aldo Esteban; Crechi, Ernesto Hector; Fassola, Hugo Enrique; Barth, Sara Regina; Colcombet, Luis; Di Rienzo, Julio (Facultad de Ciencias Forestales, Universidad Nacional de Misiones, 2022)
The objetive of this work is to present the simulator of growth and forest production called PLAFORNEA. It is a software that allows to estimate the growth of forest plantations according to the quality of the site and the management of the plantation. It serves for several species and plantin areas. It shows results of growth, biomass and timber products to be defined by length and diameter in thin tip. For each simulation, economic indicators can be estimated in order to select the most convenient management. Each simulation can be saved for later consultation or modification.